Evaluation of Standardized Ileal Digestible Tryptophan:Lysine Ratio on Growth Performance and Carcass Characteristics of Finishing Pigs Fed with or without Ractopamine HCl - J. Soto; M. D. Tokach; K. J. Touchette; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
Previous research has shown that increasing the SID Trp:Lys ratio up to 24.5% in finishing pigs fed ractopamine HCl (RAC) improved ADG by 0.15 and 0.08 lb/d in comparison with ratios of 18 and 21%, respectively. The objective of the present experiment was to determine the effects of feeding higher SID Trp:Lys ratios with and without RAC on growth performance and carcass characteristics of finishing pigs. A total of 1,101 pigs (PIC 1050 × 327, initially 218.9 lb BW) was used in a 30-d experiment. Pens of 26 pigs were randomly assigned to 1 of 6 dietary treatments arranged in a 2 × 3 factorial, with main effects of RAC (0 or 10 ppm) and SID Trp:Lys (20, 24, and 28%) with 7 replications per treatment. Diets with and without RAC were formulated to 0.90 and 0.66% SID lysine, respectively. Overall (d 0 to 30), RAC × SID Trp:Lys interactions were observed (linear, P<0.05) where increasing SID Trp:Lys ratio in pigs fed RAC improved BW, ADG, and F/G; however, these criteria decreased when pigs did not receive diets containing RAC. Similarly, RAC × SID Trp:Lys interactions were observed (linear, P<0.05) for carcass criteria with improvements in carcass ADG, carcass G:F, and HCW when pigs were fed increasing SID Trp:Lys in diets containing RAC, but not without RAC. In summary, increasing SID Trp:Lys ratio to more than 20% improved growth and carcass performance when diets contained RAC, whereas for pigs fed diets without RAC, increasing SID Trp:Lys ratio to more than 20% had poorer performance.
Keywords: growth; late finishing pig; ractopamine HCl; tryptophan